Effect of Thermal Parameters on Hydration Heat Temperature and Thermal Stress of Mass Concrete. (3rd March 2021) - Zhao, Yuqin; Li, Gaosheng; Fan, Caixia; Pang, Wentai; Wang, Yongtao
Abstract : To explore the influence of concrete thermal parameters on the hydration heat temperature and thermal stress of mass concrete, four feature positions of a dam foundation were chosen to analyze the changing process of temperature and stress by varying the thermal parameters, including the thermal conductivity, specific heat, surface heat diffusion coefficient, temperature rise coefficient, solar absorption coefficient, and thermal expansion coefficient. Some conclusions were obtained as follows. Increasing the thermal conductivity and reducing the specific heat and temperature rise coefficient of concrete can effectively reduce the maximum temperature of the central concrete structure. Increasing the solar absorption coefficient, specific heat, and thermal expansion coefficient and reducing the thermal conductivity, surface heat diffusion coefficient, and temperature rise coefficient of concrete can reduce the maximum principal tensile stress in the structure to a certain extent. The maximum principal tensile stress at different positions of the structure has a linear functional relationship with the thermal conductivity, specific heat, and thermal expansion coefficient and has a quadratic function relationship with the surface heat diffusion coefficient, temperature rise coefficient, and solar absorption coefficient. Besides, this study also proposed a series of related anticracking measures. This study was expected to provide a theoretical reference for the design, construction, and cracking disease prevention of mass concrete structures.